Decision-making in Multiple Sclerosis: The Role of Aversion to Ambiguity for Therapeutic Inertia among Neurologists (DIScUTIR MS) - Saposnik, Gustavo; Sempere, Angel P.; Prefasi, Daniel; Selchen, Daniel; Ruff, Christian C.; Maurino, Jorge; Tobler, Philippe N. (Frontiers in Neurology, 2017)
Background: Therapeutic inertia (TI) in multiple sclerosis (MS) is defined as the lack of treatment escalation when there is evidence of disease activity. Limited information is available on physician-related factors influencing TI in MS. The aim of the study was to evaluate whether physicians’ risk preferences are associated with TI in the management of MS by applying concepts from behavioral economics. Methods: A study with neurologists managing patients with MS was conducted in Spain. Participants answered questions regarding the management of 20 case-scenarios and completed three surveys and four experimental paradigms based on behavioral economics. Surveys and experiments included standardized tests to measure aversion to risk and ambiguity, physicians’ reactions to uncertainty, and questions related to risk preferences in different domains. Results: Of 161 neurologists who were invited, 136 agreed to participate, and 96 completed the survey (response rate: 60%). TI was present in 68.8% of participants. Total aversion to ambiguity and low tolerance to uncertainty were observed in 22.9% and 42.7% of participants, respectively. Aversion to ambiguity was associated with a higher prevalence of TI (86.4% with aversion to ambiguity vs. 63.5% without aversion to ambiguity; p=0.042). In multivariate analyses, aversion to ambiguity was the strongest predictor of TI (OR 7.39; 95%CI 1.40-38.9), followed by low tolerance to uncertainty (OR 3.47; 95%CI 1.18-10.2). TI was less common among neurologists with greater volumes of patients per week as well as among MS specialists. Conclusion: Therapeutic inertia is a common phenomenon affecting nearly 7 out of 10 neurologists caring for MS patients. Behavioral economics is an innovative approach that may help our understanding of decision making in MS.